Joplin, Mo., Code art. 67, § 1201 (1917) - (:unkn) unknown (My University, 1917)
Prohibited the carrying of a concealed firearm, Bowie knife, spring-back knife, razor, knuckles, bill, sword cane, dirk, dagger, slungshot, or other similar deadly weapons in a church, school, election site, court, or other public setting. Also prohibits using the weapon in a threatening manner, using while intoxicated, or selling to a minor.
Keywords: CARRY - CERTAIN PUBLIC PLACES; CARRY - DANGEROUS PERSONS; COMMITTING CRIME W/ WEAPON; TRANSFER - MINORS